Bahasa Inggris - Sugihhartati Dj., Rachmawati; Alya Celiana Dewi; Gina Salsabila (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The manufacturing industry in this research was a polyester-producing manufacturing industry generating polyester chips and polyester staple fiber. The production process used raw materials and ancillary materials. Every raw material that was processed would produce products and byproducts in the hazardous and toxic waste (HTW) category; in the form of Wastewater Treatment Plant sludge, diethylene glycol, residue from the laboratory test, incinerator ash, spin finish oil, bottles of chemical solutions, and contaminated rags. This research aimed to evaluate the implementation of the HTW management for the key activities based on the relevant regulations to prevent harm to human health and the environment. The implementation of the HTWs management activities was observed on site. The observations were then compared with the regulations, and their conformity was scored using a Likert Scale. The results of the evaluations, covering 5 key activities of the packaging and containment, collection, storing, transportation, and symbolling and labelling, gave the percentage of 90%, 91.70%, 96%, 100%, and 85.20%, respectively. The average conformity of the HTWs management with the regulations was 93% and included in the very good category. Improvements have still to be done by this industry to ensure their HTW management operates properly by reducing their wastes using the suitable methods, such as through raw material substitution, process modification to a more efficient process, and the use of environmentally friendly technology.